2000
DOI: 10.1034/j.1399-0012.2000.140407.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome for arterio‐venous fistula at the elbow for haemodialysis

Abstract: Our report supports the view that AVF at the elbow may obviate the disadvantages of AVF at the wrist in elderly patients, females and in diabetics. In this group of patients it may be preferable to create a primary AVF at the elbow rather than the wrist. Patients who have a failed attempt at creating an AVF at the wrist should undergo AVF at the elbow before the placement of a synthetic graft. This strategy will result in saving time and avoid multiple operations. There may also be a reduction in the use of sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 15 publications
0
8
1
1
Order By: Relevance
“…26 Strong associations between malnutrition, inflammation and atherosclerosis in ESRD populations suggested the presence of a syndrome we have called the malnutrition, inflammation, and atherosclerosis (MIA) syndrome. 27 Unlike the results of a UK study, 28 where serum albumin .3.5 g/dl was associated with poorer long-term patency of AVFs, our results showed that lower serum albumin levels were associated with a significantly poor patency rate of AVFs. We had no direct evidence to link hypoalbuminaemia and the inflammatory process in our patients, but we believe that inflammation might play a key role in the patency rate of AVFs.…”
Section: Discussioncontrasting
confidence: 99%
“…26 Strong associations between malnutrition, inflammation and atherosclerosis in ESRD populations suggested the presence of a syndrome we have called the malnutrition, inflammation, and atherosclerosis (MIA) syndrome. 27 Unlike the results of a UK study, 28 where serum albumin .3.5 g/dl was associated with poorer long-term patency of AVFs, our results showed that lower serum albumin levels were associated with a significantly poor patency rate of AVFs. We had no direct evidence to link hypoalbuminaemia and the inflammatory process in our patients, but we believe that inflammation might play a key role in the patency rate of AVFs.…”
Section: Discussioncontrasting
confidence: 99%
“…HAIDI is characterized by coldness, pain, cramps, altered sensibility, and diminished strength in the ipsilateral hand. Diabetics are at risk for distal ischemia as collaterals may not sufficiently compensate for this loss of perfusion in the presence of distal occlusive disease (5). Some degree of HAIDI is routinely observed in a normal ''asymptomatic'' dialysis population (6).…”
mentioning
confidence: 99%
“…In many of them, however, a peripheral radiocephalic fistula will not mature, if the artery exhibits extensive medial calcification and has lost its capacity to dilate and undergo progressive remodelling. For these patients a more central AVF at the cubital fossa is a good alternative [20,33]. The risk that a steal syndrome develops in patients with an elbow fistula is 4-fold higher, however, compared with patients with a peripheral AVF [37].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Nevertheless, the use of CVC for chronic haemodialysis has been recommended for children and for elderly patients, for patients with severe heart failure and limited life expectancy, for those with repeated episodes of access thrombosis due to low blood pressure or hypercoagulability, and for patients in whom creation or maintenance of an av-access is difficult or impossible due to exhausted peripheral veins or due to severe peripheral arterial occlusive disease (PAOD) and in steal syndrome [5,[16][17][18][19][20][21]. Before blindly following these recommendations (and thereby providing the majority of ESRF patients with CVC access for haemodialysis), one should perhaps look for possible vascular surgical alternatives.…”
Section: Introductionmentioning
confidence: 99%